Optical Cable Backbone Network Design In The Province Kalimantan South Use Technology DWDM OTN - Charla Tri Selda Manik; Azarya NJ Siahaan; Saut Situmorang (PT Inovasi Pratama Internasional, 2021)
In designing the backbone network for the province of East Kalimantan using Dense Wavelength Division Multiplexing (DWDM) and Optical Transport Network (OTN) devices which cover 10 districts and cities consisting of 34 segments, of which 34 segments consist of 10 OTN DWDM sites and 16 Optical Land Amplifier sites ( OLA). From the results of the design and simulation of the backbone network, it was found that the value of the Optical Link Power Budget (OLPB) < 50 dBm where this value is the ideal value in deploying a DWDM OTN backbone network, and the range of the Optical Signal Noise Ratio (OSNR) is between 20 dBm < OSNR < 40 dBm, which is the ideal value for OSNR, and has an Optical Rise Time Budget (ORTB) < 60 ps, and also has a segment margin system of > 7 dB.